2010
DOI: 10.1002/cncr.25211
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of molecular human leukocyte antigen typing and outcome in high‐risk melanoma patients receiving adjuvant interferon

Abstract: BACKGROUND: Interferon is approved for adjuvant treatment of patients with stage IIB/III melanoma. The identification of predictive markers that would permit selection of patients would be beneficial. Specific human leukocyte antigen (HLA) class I and II antigens have previously shown an association with response to therapy or overall survival of patients with metastatic melanoma. METHODS: A total of 284 high-risk melanoma patients participating in a randomized trial an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…The determination of HLA is also a factor predicting recurrence in patients treated with interferon 2b as adjuvant treatment. The percentage of relapses is significantly lower in patients with HLA genotype A33, HLA B57, HLA-Cw03, and HLA-Cw06 [65].…”
Section: Adjuvant Treatment Withmentioning
confidence: 87%
“…The determination of HLA is also a factor predicting recurrence in patients treated with interferon 2b as adjuvant treatment. The percentage of relapses is significantly lower in patients with HLA genotype A33, HLA B57, HLA-Cw03, and HLA-Cw06 [65].…”
Section: Adjuvant Treatment Withmentioning
confidence: 87%
“…Irrespective of the precise mechanism, the existence of a distinct and identifiable subset of patients with clinical benefit from allogeneic vaccination suggests continued exploration of immune-based adjuvant strategies in melanoma, with particular reference to melanoma-associated antigens present in Melacine and presented by HLA-A2 and HLA-Cw3. Moreover, the possibility of interactions between HLA haplotype and treatment with other types of immunotherapy, such as IFNα, ipilimumab, IL-2, anti-PD-1 or anti-PD-L1 antibody therapies, may deserve further study, although previous efforts to find such interactions have been inconclusive (14,15). …”
Section: Discussionmentioning
confidence: 99%
“…In another study assessing HLA alleles, a total of 284 high-risk melanoma patients participating in a randomized trial of HD-IFN compared with observation were typed for HLA class I and II. Patients positive for the Cw 06 allele had a significant advantage in median RFS (100.2 versus 37.3 months) and median OS (not reached versus 78.9 months) [83].…”
Section: Predictive and Prognostic Factors In Patients Treated With Imentioning
confidence: 93%
“…Patients homozygous for rs10964859 (HR = 2.01, 95% CI 1.17, 3.44; p = 0.01) and rs10964862 (HR 1.84, 95%CI 1.03, 3.27, p = 0.04) were associated to increased risk of death following metastasis Gogas et al [83] HLA gene The median relapse-free survival of the Cw 06-positive cohort was 100.2 months versus 37.3 months in the Cw 06-negative cohort (p = 0.013) Hofmann et al [86] Serum cytokines At baseline, the combination of TNF-a, B2 M and sIL-2R revealed a positive predictive value for relapse of 82.9% in the multivariate analyses lost, thereby demonstrating the lack of usefulness of serum autoantibodies as a prognostic factor [84].…”
Section: Referencementioning
confidence: 98%